Structural and functional analysis of the socio-psychological status of a group subject - Boubnov, Alexander L. (Izvestiya of Saratov University Philosophy Psychology Pedagogy, 2022)
Introduction. For the first time the approach was proposed to the study of the socio-psychological status of a group subject, in which the status is understood as a systemic formation reflecting accordingly business, axiological, formal-hierarchical and attraction-expressive aspects of the group position in the basic organization. Theoretical analysis. Through the theoretical structural and functional analysis the structure of group status (includes activity, value, cognitive and emotional components) and its main functions (behavioral-regulative, cognitive-evaluation, normative-stratification and identification-orientation) are identified. The assumption of possibility of correlation of the most expressed components of the status, defining one or the other level of its status, and dominance of certain functions is put forward. Empirical аnalysis. The empirical study of group status was conducted on the material of student groups with the help of K. M. Gaidar socio-psychological questionnaire for determining the socio-psychological status of a group subject. With the help of cluster and factor analysis for the first time the peculiarities of the configuration of the components of the groups status with its high, medium or low level are revealed. Conclusion. As a result, it was found that its particular level is determined by a combination of several structural components. As prospects for the further research of the problem under study, the identification of the functions of the status of a group subject that dominates at a certain level of this status is indicated.